Floral micromorphology and transcriptome analyses of a fragrant Vandaceous Orchid, Vanda Mimi Palmer, for its fragrance production sites - Toh, Conie; Ab. Rahim, Mohd Hairul; Mohd. Ain, Nooraini; Namasivayam, Parameswari; Go, Rusea; Abdullah, Nur Ashikin Psyquay; Abdullah, Meilina Ong; Abdullah, Janna Ong (BioMed Central, 2017)
Background: Vanda Mimi Palmer (VMP) is commercially valuable for its strong fragrance but little is known regarding the fragrance production and emission sites on the fowers. Results: Olfactory perception detected fragrance only from the petals and sepals. Light and Environmental Scanning Electron microscopy analyses on fresh tissues showed distributions of stomata and trichomes concentrated mostly around the edges. These results paralleled the rich starch deposits and intense neutral red stain, indicating strong fragrance and trichomes as potential main fragrance release sites. Next Generation Sequencing (NGS) transcriptomic data of adaxial and abaxial layers of the tissues showed monoterpene synthase transcripts specifcally linalool and ocimene synthases distributed throughout the tissues. qPCR analyses taken at diferent time points revealed high levels of linalool and ocimene synthases transcripts in the early morning with maximal level at 4.00 am but remained low throughout daylight hours. Conclusions: Knowledge of the VMP foral anatomy and its fragrance production characteristics, which complemented our previous molecular and biochemical data on VMP, provided additional knowledge on how fragrance and fower morphology are closely intertwined. Further investigation on the mechanisms of fragrance biosynthesis and interaction of potential pollinators would elucidate the evolution of the fower morphology to maximize the reproduction success of this plant.